Owl Aeroacoustics: Analysis of a Silent Flight - M. Mozafari; M. Masdari (مهندسی مکانیک شریف, 2023)
The owl is renowned as nature's stealth bird and possesses distinctive aeroacoustic qualities. When it comes to the silent flight of owls, two primary hypotheses are considered: the self-masking hypothesis and the stealth hypothesis. Consequently, our intention is to present a comprehensive review article on the aeroacoustics of owls. This paper provides a concise overview of research conducted using Open Source Intelligence (OSINT) studies and visualization techniques, delving into how owls achieve silent flight and how their noise reduction mechanisms can be applied in engineering designs. The objective is to examine the distinctive physical characteristics of owls, their foraging behavior, and their ability to maintain silence in the presence of other species. Subsequently, the focus shifts to an analysis of the noise generated during owl flight, with emphasis on the geometric aspects of their wings, which play a crucial role in enabling silent flight. The subsequent sections provide an overview and summary of efforts to model the wing characteristics responsible for silent flight, as well as a description of noise reduction technologies inspired by owl features. In general, there exists a wide range of hypotheses regarding the silent flight and stealth of owls; however, the most compelling and well-supported explanations to date revolve around three key factors: the serrated structure of the wing leading edge, the velvety fibers and fringes along the trailing edge, and the combined effect of trailing edge and leading edge serrations. These factors contribute to a significant reduction in overall sound pressure levels across all angles of attack, stabilize speed fluctuations on the suction surface, and eliminate low and high-frequency sounds. Additionally, owls possess long velvety feathers on their wings, which absorb sound frequencies, and the elongated distal barbules create a multi-layered porous structure that enhances sound absorption.